PENERAPAN MODEL QUANTUM TEACHING DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI 004 SEI BEBERAS HILIR KECAMATAN LUBUK BATU JAYA - Siti Suwarsih; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstraction: the main purpose of this classroom action research is increasing student s’ achievement in learning social subject for fourth year students of SDN 004 Sei Beberas Hilir Kecamatan Lubuk Batu Jaya by implementing Quantum Teaching Model. This research is classroom action research which contain with two cycles. Every cycle consists of four phases. They are planning, implementation, observation and reflection. The subject of the research is fourth years’ students of SDN 004 Sei Beberas Hilir. They are 32 students as subject. The instrument of collecting data which is applied is a test to measure the achievement in studyingSocial subject, observation project to measure study activities. Data analyzing techniquewhich is applied is qualitative and quantitative data analysis. The result of the research shows that implementing Quantum Teaching Model can increase the student achievement in learning Social subject. It can be proven by (1) the average class score increases from initial test 68,4 become 73,9 in first cycle and in the second cycle become 86,4. From the average score that is reached, is there any increase as 8,04% in first cycle and 18,28% in second cycle. (2) The passing grade of the student classically (KKM 75) in initial test 43,75. In First cycle test is 53,13%. After reflection to 15 students who did not pass, (the score below 75) and at the second cycle test is 96,88%. After doing reflection for whole students, their study achievement has increased. It can be seen from the percentage of the students’ completeness. (3) in student learning activities also showed enhancement. In first phase the percentage of learning activities of the students is 68,75% whereas in second phase reached 90% so the enhancement student learning activities is 21,25%. Whereas in teaching activities of the teacher increase in first phase is 76,25% and in second phase increase to 88,75% so the enhancement that teacher did is 12,5%. Keyword: Quantum teaching model, learning social subject